Chronically increased osteoclastogenesis in adult celiac disease patients does not hinder improvement in bone health induced by gluten-free diet: Role of vitamin D, OPG and IL-6 - Skubica, Patrik; Hoffmanova, Iva; Dankova, Pavlina (The Journal of nutritional biochemistry, 2025)
The etiology of bone loss in celiac disease (CeD) remains a clinical challenge, with uncertainties present such as the extent of involvement of malabsorption and inflammation-induced osteoresorption processes in development of osteopenia/osteoporosis (OPN/OP), or reasons for failure to achieve healthy bone mass (BMD) even after long-term gluten-free diet (GFD) treatment. This observational prospective study explores the in vitro osteoclastogenic potential of peripheral blood precursors originating from adult active (newly diagnosed and untreated) celiac disease patients (aCeD) and describes the longitudinal changes in osteoclastogenesis after long-term adherence to GFD. To find connections between in vitro observations and in vivo bone metabolism changes, serum levels of 25(OH)D3, PTH, bCTX, PINP, CRP, IL-6, RANKL and OPG were measured before and after GFD and levels of these markers were correlated with the rate of osteoclastogenesis in vitro. OPG and IL-6 showed associations with BMD and/or presence of OPN/OP. Patients after GFD (CeD-GFD) exhibited improved BMD and increased serum 25(OH)D3 levels, alongside reduced bCTX and PINP levels. Compared to healthy donors, aCeD osteoclast genesis in vitro was higher and, surprisingly, remained elevated even in CeD-GFD patients. Negative correlation was found between osteoclastogenesis rate and serum OPG in aCeD, while osteoclastogenesis rate positively correlated with PTH in CeD-GFD. These results highlight OPG as marker for risk of OPN/OP in CeD and suggest that improvement of BMD after GFD is a result of uncoupling between bone metabolism and osteoresorptive action of osteoclasts after GFD.
Keywords: dospělí; Female; Diet, Gluten-Free; Adult; parathormon; osteogeneze; mladý dospělý; ženské pohlaví; Celiac disease; kostní denzita; Bone Density; Osteoclasts; kosti a kostní tkáň; lidé; Bone metabolism; vitamin D; osteoprotegerin; Osteoporosis; Interleukin-6; osteoklasty; Osteoclastogenesis; Vitamin D; Parathyroid Hormone; prospektivní studie; Male; Prospective Studies; Young Adult; interleukin-6; bezlepková dieta; Celiac Disease; lidé středního věku; Osteogenesis; Gluten-free diet; mužské pohlaví; Bone and Bones; Middle Aged; Osteoprotegerin; celiakie; Humans